Ultrastructural remodelling of e ndoplasmic reticulum-derived membranes and hepatitis C virus morphogenesis in human liver samples - Falcón Cama, Viviana; Acosta-Rivero, Nelson; González Pozos, Sirenia; Dueñas-Carrera, Santiago; Acosta Medina, Emilio; Kourí Flores, Juan (Revista Cubana de Medicina Tropical, 2017)
Introduction: hepatitis C virus infection is considered as a leading cause of liver disease worldwide. Despite recent advances in understanding the hepatitis C virus life cycle using the highly replicative JFH1 strain in human hepatoma cells, little is known about hepatitis C virus morphogenesis. Low levels of hepatitis C virus assembly in this cell culture model as well as low levels and complexity of hepatitis C virus particles in infected humans and chimpanzees have hampered the study of hepatitis C virus morphogenesis in vivo. Objetivo: to study the ultrastructural features and viral assembly events in hepatocytes from HCV hepatitis C virus-infected patients. Methods: liver needle biopsies samples of patients with hepatitis C virus infection, specific antibodies against hepatitis C virus and transmission electron microscopy and immunoelectron microscopy analyses were used in this study. Results: ultrastructural studies in liver biopsies from hepatitis C virus-infected patients revealed that hepatitis C virus infection was related with remodelling of endoplasmic reticulum-derived membranes and with a variety of cytoplasmic microenvironments in hepatocytes. Dilated endoplasmic reticulum and formation of various membrane vesicles are features that have been associated with the viral replication complex. Interestingly, hepatitis C virus-like particles and core-like particles budding and assembly were observed near convoluted electron-dense membranes and tubular structures. Particularly, hepatitis C virus structural proteins localize to the endoplasmic reticulum. Conclusions: these events indicate that hepatitis C virus nucleocapsids and early virion assembly take place at endoplasmic reticulum membranes that are associated with these cytoplasmic microenvironments in human hepatocytes.